Avaliação de fitases microbianas em dietas de frangos de corte - Pinto, Gabriel Villela Dessimoni [UNESP] (2015)
The objective of this study was to evaluate phytases from different microorganisms on performance, bone characteristics, excretion and digestibility of nutrients, as well as phosphorus bioavailability and costs. The standard curve method was used to obtain the phosphorus bioavailability in response of performance and bone mineralization. The study was divided in four trials. In the first study were evaluated phytases from Buttiauxella sp (A; expressed in Trichoderma reesei) and E. coli (B; expressed in S. pombe) origins. A total of 2,160 male day-old Cobb 500 chicks were distributed in a completely randomized design to nine treatments and eight replicates containing 30 birds each. The treatments were: T1 - Positive Control (PC) - meeting all requirements of the birds; T2 - Negative Control 1 (NC1) - reduction of 0.14% P and 0.13% Ca; T3 - Negative Control 2 (NC2) - reduction of 0.17% P and 0.16% Ca; T4 - NC2 + phytase A (250 FTU/kg); T5 - NC2 + phytase A (500 FTU/kg); T6 - NC2 + phytase A (1000 FTU/kg); T7 - NC2 + phytase B (250 FTU/kg); T8 - NC2 + phytase B (500 FTU/kg); T9 - NC2 + phytase B (1000 FTU/kg). Regressions were performed on performance data, bone mineralization and excretion of nutrients to determine the optimal level inclusion of each phytase. A second trial was conducted to evaluate the response of the inclusion of a new bacterial phytase (E. Coli) supplemented on diets meeting all requirements of the birds, or with nutritions reduction. A total of 896 male day-old Cobb 500 broilers were divided into 32 experimental units, each unit consisting of 28 birds. The design was completely randomized with four treatments and eight replications. The treatments were: Positive Control (PC) - diet meeting the nutritional requirements of the birds; Negative Control (NC) - reduction of 100kcal ME/kg; 0.14% avP and 0.11% Ca; NC + Phy (500FTU/kg); PC + Phy (500FTU/kg). The third trial was conducted to evaluate the inclusion of ...